Historical architectural rules when designing buildings (Journal of Architectural Design, 2021)
This article is about the first hospital built in Samarkand - "Bemoristan" by Ibrahim Tamgochkhan through scientific research and graphic reconstruction of its architecture, a building that is very unique for the history of Uzbekistan and the science of architecture, but the building that has not survived to our times is intended to popularize it among the general public and put into scientific circulation.